Isolation of genomic dna from fruit bats of kelabit Highlands for dna archiving and determination of Genetic variation - Mohd Azib, Salleh; Edmund Sim, Ui Hang; Mustaffa, Abdul Rahman; Mohd Tajuddin, Abdullah (ASEAN Review of Biodiversity and Environmental Conservation (ARBEC), 1999)
A total of 40 fruit bats belonging to five species, namely Cynopterus brachyotis (34), Aethalops alecto (3), Pipistallus tenius (1), Balionycteris maculata (1) and Megaerop ecaudatus (1) were captured from two sites during the expedition to Bario in April 1995. Whole blood and liver tissue samples were taken from freshly killed bats and stored in liquid nitrogen in the field before transferring to a - 70ºC deep freezer in the laboratory. Genomic DNA was successfully isolated from whole blood samples derived from 13 bats using SDS-lysis followed by phenol-extraction methods. Pure DNA samples were dissolved in tris-EDTA buffer and stored at -20ºC for DNA archiving and determination of genetic variations within and between the different species